Lipid metabolism-related genes in the pathogenesis of keloid: Based on bioinformatics analysis and validation - Yixiu ZHONG; Qi WANG; Jianglin ZHANG (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2024)
Objective To explore lipid metabolism-related genes that contribute to the development and progression of keloid based on bioinformatics. Methods The keloid related datasets were obtained from the GEO database, while lipid metabolism-related genes were downloaded from the Genecards database. Intersection analysis was performed to screen for common genes. GO and KEGG enrichment analyses of differentially expressed genes were performed. Significant differentially expressed genes were validated using real-time fluorescence quantitative PCR (qRT-PCR) and immunohistochemistry. Results ACSS3 and PRKD1 were the two common genes related to lipid metabolism in keloid, with ACSS3 showing the most significant difference. The biological processes of differentially expressed genes were mainly enriched in the biosynthesis of glycerides and the metabolism of fatty acid derivatives. KEGG pathways were mainly associated with the processes of glyceride metabolism and arachidonic acid metabolism. Immunohistochemistry and qPCR revealed high expression levels of ACSS3 in keloid tissue. Conclusion ACSS3 may play an important role in the occurrence and development of keloid by affecting lipid metabolism.